2013
DOI: 10.2174/1871527311312040016
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Weaknesses of Cerebrospinal Fluid Biomarkers in Alzheimer’s Disease and Possible Detection of Overlaps with Frailty Process

Abstract: With the increase of human lifespan and refinement of diagnostic techniques dementia, and Alzheimer's disease (AD) in particular, have become a multi-decade process with a complex pathogenesis. The prognosis of AD patients, especially in late stages, may be strongly influenced by factors that go far beyond the well-recognized cascades (tau deposition, amyloid plaques). In this context, AD and Frailty, a multidimensional process of the elderly, inevitably overlap. Not surprisingly, the routine biomarkers collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Major effort should be launched for assessing to what extent the impact on sleep and cognition, as detailed in our hands, may in fact be replicated by other teams utilizing different trajectories; for the time being, whether some of the NM benefits described (i.e., changes of sleep structure) are really target-dependent and/or, at least in part, frequency-dependent, might be addressed. In addition, the significance of clinical changes in cognitive performance need to be evaluated in light of real changes in routine functional way of life (as explored on dementia in Stefani et al, 2013). On-going studies and extended follow-up will contribute at clarifying this issue.…”
Section: Resultsmentioning
confidence: 99%
“…Major effort should be launched for assessing to what extent the impact on sleep and cognition, as detailed in our hands, may in fact be replicated by other teams utilizing different trajectories; for the time being, whether some of the NM benefits described (i.e., changes of sleep structure) are really target-dependent and/or, at least in part, frequency-dependent, might be addressed. In addition, the significance of clinical changes in cognitive performance need to be evaluated in light of real changes in routine functional way of life (as explored on dementia in Stefani et al, 2013). On-going studies and extended follow-up will contribute at clarifying this issue.…”
Section: Resultsmentioning
confidence: 99%
“…These include routine screening of the general population, patients seen in primary care or nursing home residents ( Woods et al, 2003 ; Lliffe and Manthorpe, 2004 ). It should be noted that biomarkers with good properties of sensitivity and specificity and readily applicable to asymptomatic or early symptomatic populations at risk are not yet available ( Risacher and Saykin, 2013 ; Stefani et al, 2013 ). This leads to an initial disease suspicion still based on cognitive and/or functional complaints that are noticed by patients and/or relatives and considered abnormal enough to seek a consultation ( Weir et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a growing interest in biomarkers of neurodegenerative diseases [12,13] the correlation between vitamin D deficiency and neurodegeneration is becoming the real hot topic. Scientific literature in the last years emphasized the correlation between Alzheimer Disease (AD) and low levels of vitamin D. Recent meta-analyses confirmed that low serum vitamin D concentrations are associated with the impairment of specific cognitive domains, such as memory and executive functions [14,15].…”
Section: Introductionmentioning
confidence: 99%